Pengaruh Media Papan Pecahan Terhadap Kemampuan Pemahaman Materi Pecahan Sederhana Siswa Kelas III Sekolah Dasar - Suci Ulandani; Maulina Hendrik; Yorenza Meifinda (Universitas Muhammadiyah Bangka Belitung, 2024)
This research is driven by the low level of students' understanding of simple fractions in mathematics, which can affect their overall learning achievement. The aim of this study is to determine the impact of using fractional board media on the conceptual understanding of simple fractions among third-grade students at SD Negeri 6 Simpangkatis. A quantitative research approach with an experimental design method, specifically the One Group Pre-Test Post-Test Design, was employed. The sample comprised all third-grade students at SD Negeri 6 Simpangkatis, selected through a saturated sampling technique. Data analysis included descriptive statistics, normality tests, and hypothesis testing using paired sample t-tests. Data was collected using essay tests that assessed the level of conceptual understanding and student success. The results indicated that the paired sample t-test showed t-hitung > t-tabel (2.749 > 1.713), leading to the acceptance of the Ha hypothesis. Thus, it can be concluded that the fractional board media positively impacts students' ability to understand simple fractions in the third grade at SD Negeri 6 Simpangkatis.